Eight Annual AACR International Conference on Frontiers in Cancer Prevention Research Houston, Texas, U.S.A. 06-09 Disember 2009 - Md. Azman PKM Seeni, Mohamed (Pusat Pengajian Sains Perubatan, 2009)
Eptdemrologrcal studres have demonstrated a posrtNe cooeldtion between consumption of vE'(jeldbles, frurts and bevt:r ages with reduced mk of canre. It 1s esumated there are around 8,100 plant speer~ 'in the Mal.~ysian rain forests. wrth 1 0% of them reported to have some medicinal value. HOWE'\Ier, to date m Malaysta, not much investigdtion has been donP on chE>mopreventiw actrvitrP.S on cancer although Malaysran plants are an exclusrve !.Ottrce of effe<trve themopreventrve agents and therefore. thrs batkground leads to the premrse that our local plants such as Streblus asper could have greater potentral for the chemoprevention a<tJVrlles. Streblus asper rs well known as an expensrve bon~11 plant whrch rs rndrgenous to tropccal countnes such as Malaysia. Thailand. Srr Lanka and lndra It rs used tradiuonally rn leprosy. pries. drarrhea. dysentery. elephantrasis and cancer tt finds place in AyurvediC Pharmacopoeia of India and also been descrrbed m some monographs, but none have reported rts activity as chelllOpfeventive ~ts and the underlyrng me<hanisms remarn undt>ar In the present study, we try ro identify its brologrcal properues and the cytotoKrdty efle<t on normallrver and kidney cells. Us1ng the osteosarcoma cells as our 1n vrtlo model, the ICSO of Streblus asper root eXtract was deterrnrned and observed rts efle<t on the osteosarcoma cells morphology that changes w1thrn trme. the anu prolifer atrve pattern and live-death analysis under confocal mrcroscope analysrs. The results showed thdt the root extracts drd not contarned any heavy metals compound such as mercury and cadmium and With less arsenrc (0 02 ppm) clnd plumbum (0.07 ppm) and ~ing non·<)'totoxrc effect on vero cells (normal krdney cells} and WRL·68 (E'tls (normal liver cells) Our HPLC profiling analysrs also r!'Vealed antroxidants compounds exrst rn the Streblus asper root extracts such as caffeic acid which has been shown to dCI as a carcrnogenrc rnhibrtOI Although the low·fevef of antr-oxrdants been found from the extracts but rt strll can rnhrbrt thl' growth of the osteosarcoma cells wtuch also exerl dpoptosis features l1ke cell sh11nkage (atrophy) and vocalizatron rn trme and dose-dependent manner The plant extracts IC50 doses was Jt 0.05% of root extracts and rt also demonstrated the ant•·prolifLoratrve effe<t by suppressed the cells growth as early as 12 hours of treatment and marked cell death t1il day 6 On live'ileath analys~s under confocal mrcroscope usrng Calcern and Ethrdrum starnrng confrrmed that Streblus asper root extract exer1 cell death to osteosarsoma cells. This study IS Just a prelimrnary study as to identrfy rts pharmucologrcal propertres on c,:~~crnogenesrs and further rnvestrga110n rs strll on-gorng to develop rt as the chemopreventrve agent espec:ialty to determrne the srgnaling pathway involved